Efektivitas Penyelenggaraan Pelatihan Revolusi Mental di Pusat Pelatihan dan Pengembangan Kajian Manajemen Pemerintahan Lembaga Administrasi Negara Kota Makassar - Muh Ikhsan Alfarabi; Muhlis Madani; Rasdiana Rasdiana (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
This study was to find out how the effectiveness and to describe and analyze the effectiveness of organizing mental revolution training at the Center for Training and Development of Government Management Studies, Makassar City State Administration. This study used a descriptive qualitative research based on data using purposive sampling technique. The focus of this study was the reaction of participants to the instructor, materials, methods, and facilities and infrastructure. Data collection techniques used methods, namely, observation, interviews and documentation related to the implementation of mental revolution training at the KMP LAN RI Research Center for Makassar City. The results showed that the implementation of mental revolution training at the KMP LAN RI Center for Research and Development in Makassar had been effective. This was because all reaction indicators that support the effectiveness of a training had been fulfilled, namely instructors, materials, methods, and facilities and infrastructure. Where the participants' reactions to all reaction indicators were very positive and motivating during the Mental Revolution training.Keywords: Effectiviness, Training